AB0952 Subclinical Left Ventricular Dysfunction in Patients with Ankylosing Spondylitis without Clinically Evident Cardiovascular Disease: A Two-Dimensional Speckle Tracking Echocardiographic Study. (10th June 2014) - Ustun, N.; Kurt, M.; Yagiz, A.E.; Guler, H.; Turhanoglu, A.D.
Abstract : Background: Cardiac involvement is common in ankylosing spondylitis (AS), which has not been previously evaluated by using speckle tracking echocardiography (STE). Objectives: The objectives of this study were to evaluate the left ventricle (LV) systolic strain by STE in order to provide the subclinical myocardial dysfunction in patients with AS and to examine the relationship between LV systolic strain and disease activity indices. Methods: A total of 26 patients with AS without clinically evident cardiovascular disease and 26 age-, sex-, and BMI-matched healthy controls were included in the study. Bath AS disease activity index, Bath AS fuctional index, Bath AS metrology index and Bath AS radiologic index were used as clinical indices. Conventional echocardiography, tissue Doppler imaging, color tissue Doppler derived strain/strain rate echocardiographic imaging were performed by a single cardiologist using a 2.5–3.5 MHz transducer and Vingmed System 7 (Vivid 7 Pro; Horton, Norway). All data were transferred to a workstation for further offline analysis (EchoPAC 6.1; GE Vingmed Ultrasound AS). For left ventricle color tissue Doppler dynamic images were obtained from from LV apical 4-, 3- and 2-C (chamber) views. Results: There were no significant differences in baseline demographic characteristics and cardiovascular risk factors between the patients and the controls. There were no significant differences between patients and controls in terms of left ventricle diameters, ejection fraction, posterior wall thickness, interventriculer septum wall thickness, mitral deceleration time and systolic myocardial flow velocity (p>0.05). AS patients were observed to have statistically significantly lower left ventricule peak longitudinal and global strain/strain rate values in the 4C, 3C, and 2C views compared with the controls (p>0.05). In addition, we detected no correlation in left ventricule global strain values and AS clinical indices values (p>0.05). Conclusions: Myocardial systolic function assessed by STE, which is a sensitive marker of ventricular dysfunction is impaired in AS. References: Teske AJ, De Boeck BW, Melman PG, Sieswerda GT, Doevendans PA, Cramer MJ. Echocardiographic quantification of myocardial function using tissue deformation imaging, a guide to image acquisition and analysis using tissue Doppler and speckle tracking. Cardiovasc Ultrasound 2007;5:27. Schiller NB, Shah PM, Crawford M, et al: American Society of Echocardiography committee on standards, subcommittee on quantitation of two-dimensional echocardiograms: Recommendations for quantitation of the left ventricle by two-dimensional echocardiography. J Am Soc Echocardiography 1989;2:358–367. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1961